Time of Change: Health Effects of Motherhood - Fabian T. Dehos; Marie Paul; Wiebke Schäfer; Karolin Süß (Institute of Labor Economics (IZA), 2024)
This paper combines German claims and survey data to provide a comprehensive picture of the health dynamics surrounding the transition into motherhood. Event-study estimates reveal good mental health around birth, but declines afterward, as reflected by increasing mental illness diagnoses and antidepressant and psychotherapy use during the first four years of motherhood. Painkillers, headaches, obesity, and other potentially stress-related physical illnesses, as well as survey evidence on well-being, show a similar pattern. A sustained reduction in sleep, sports, and other leisure activities, coupled with childcare obligations and possible psychosocial distress, may contribute to the long-term adverse effects of motherhood.
Keywords: J13; I10; I12; 330; mental health; maternal health; claims data